Fostering Scientific Creativity in Teaching and Learning Science in Schools: A Systematic Review - Sidek, Rubaaiah; Halim, Lilia; Buang, Nor Aishah; Mohamad Arsad, Nurazidawati (Jurnal Penelitian dan Pembelajaran IPA, 2020)
Fostering creativity among the students will result in the production of a skillful workforce and human capital in the future. Creativity is a concept that has its roots in specific knowledge domains or disciplines including scientific creativity that is specific to science. This article attempts to fill the gap in understanding and identifying the factors and pedagogical approaches that influence and facilitate the effort to foster scientific creativity in science teaching and learning in schools. Thus, the questions arise of what pedagogical approaches and factors that foster students’ scientific creativity as well as support the teaching and learning in science classrooms. A systematic review of 30 studies was conducted to investigate effective interventions and variables that influence scientific creativity among students in school science classrooms. Pedagogical approaches and strategies such as teaching creative thinking techniques, problem-based, project-based, model-based, ICT-based, integrated STEM-based, and collaborative learning were found to improve scientific creativity among students. Meanwhile, students’ factors, teachers’ factors, and environmental factors were identified to facilitate the inculcation of creativity in science teaching and learning. This review suggests that the role of teachers is crucial in fostering scientific creativity in the science classrooms and there is a need to study teachers’ beliefs and practices in real settings. Also, future studies could also focus on identifying constraining factors that may hinder the fostering of scientific creativity by teachers in the classrooms.